(untitled) (Baghdad Science Journal, 2017)
In this study a concentration of uranium was measured for twenty two samples of soil distributed in many regions (algolan, almoalmeen, alaskary and nasal streets) from Falluja Cityin AL-Anbar Governorate in addition to other region (alandlos street) as a back ground on the Falluja City that there is no military operations happened on it. The uranium concentrations in soil samples measured by using fission tracks registration in (PM-355) track detector that caused by the bombardment of (U) with thermal neutrons from (241Am-Be) neutron source that has flux of (5×103n cm-2 s-1). The concentrations values were calculated by a comparison with standard samples. The results shows that the uranium concentrations algolan street varies from(1.976- 2.736ppm), almoalmeen street varies from (1.895-2.614ppm), and alaskary street varies from (1.657-2.476ppm), and nasal street (1.657-2.476ppm) the average uranium concentration in other region (alandolos) (0.736-1.588ppm). As a conclusion from the study uranium concentration in the four region above that have military operations is relatively higher than back ground